A refined metric for multi-GNSS constellation availability assessment in polar regions. Issue 3 (1st August 2020) - Zhang, Qinghua; Chen, Zhengsheng; Cui, Yang; Zheng, Xiaolong; Rong, Fengjuan; Sun, Yangyang; Gao, Lei
Abstract: Human activity in the polar regions is increasing, and as a result of this, the positioning performance of global navigation satellite systems (GNSSs) in these regions is attracting more attention. Since the constellation design of GNSS systems (such as GPS, GLONASS, Galileo, and BDS) only provides superior coverage for human activity in the middle and low latitudes, the elevation angles of GNSS satellites are lower in the polar regions. In this study, the authors first analyzed the availability of GPS, GLONASS, Galileo, and BDS in the polar regions using the classic geometric dilution of precision (GDOP) metric. It was discovered that if only a stand-alone navigation system is employed, satellite visibility in the Arctic and Antarctic regions is excellent, but the GDOP is much higher than in the middle and low latitudes areas. Another interesting phenomenon is that a single navigation system other than GPS (i.e., GLONASS, Galileo, or BDS) will have some areas that cannot be located in the middle and low latitudes and will not appear in the polar regions. A simple solution of this problem is to combine multiple navigation systems to attain better GDOP. In reality, there are currently few achievable or practical solutions for the weight ratio of different satellites in the actual multi-system combined GDOP algorithm. Based on the signal-in-space analysis of different GNSS satellites, the authors propose a NEW WDOP metric for the spatial constellation configuration of multi-GNSSs, including detailed mathematical models and algorithms. The NEW WDOP metric was then used to assess the availability of multi-GNSSs in the polar regions with dual-system, three-system, and four-system combinations. This study thus draws some conclusions using the NEW WDOP model and measured data. In particular, when navigating and positioning in polar regions with a stand-alone GNSS, the mean of the NEW WDOP values is approximately 2.5, and there are many outlier values. Meanwhile, the mean of the NEW WDOP values with the dual GNSS combinations is <1.5, but the value of the NEW WDOP for some combinations in the polar regions is still extremely large and contains some outliers. However, the mean of the NEW WDOP with the three-system or four-system combinations in the polar regions is approximately 1, and the number of outliers is very small; in particular, the four-system combination has no outliers. The results of this study contribute some useful information for the GNSS application of multi-system combinations and satellite selection in the polar regions.